Structural and functional properties of arteries in COVID-19 survivors - V. E. Oleinikov; I. V. Avdeeva; K. N. Polezhaeva; K. I. Pavlenko; N. A. Borisova; A. A. Khromova; A. V. Kulyutsin (Кардиоваскулярная терапия и профилактика, 2023)
Aim. The study of the structural and functional properties of arteries in patients after a coronavirus disease 2019.Material and methods. The study included 113 people: 45 people who were examined before the start of the COVID-19 pandemic, healthy individuals who had COVID-19 (n=44), 24 patients with hypertension (HTN) in combination with prior COVID-19. In the individuals included in the study, the blood tests were performed, while the carotid arteries were evaluated using high-RF signal technology, applanation tonometry, volume sphygmography, and a test with post-occlusive reactive hyperemia were performed.Results. According to the study of carotid arteries, significant differences were registered between groups of healthy individuals (with and without a history of COVID-19) and HTN patients after COVID-19. According to the applanation tonometry in patients with hypertension and COVID-19 in history, aortic pressure and carotid-femoral pulse wave velocity significantly exceeded those in cohorts of individuals without cardiovascular diseases. According to the results of volume sphygmography in the group of patients after COVID-19, signs of early vascular aging were revealed, and the maximum values of these indicators were recorded in the group of hypertensive patients.Conclusion. The results obtained in the course of this study make it possible to state an increase in the arterial stiffness in people after COVID-19, which can be regarded as a sign of early vascular aging.